Spatially resolved Raman spectroscopy of defects, strains, and strain fluctuations in domain structures of monolayer graphene - Lee, Taegeon; Mas'ud, Felisita A.; Kim, Myung Jong; Rho, Heesuk (NATURE PUBLISHING GROUP, 2017)
We report spatially resolved Raman scattering results of polycrystalline monolayer graphene films to study the effects of defects, strains, and strain fluctuations on the electrical performance of graphene. Two-dimensional Raman images of the integrated intensities of the G and D peaks (I-G and I-D) were used to identify the graphene domain boundaries. The domain boundaries were also identified using Raman images of I-D/I-G and I-2D/I-G ratios and 2D spectral widths. Interestingly, the I-D maps showed that the defects within individual domains significantly increased for the graphene with large domain size. The correlation analysis between the G and 2D peak energies showed that biaxial tensile strain was more developed in the graphene with large domain size than in the graphene with small domain size. Furthermore, spatial variations in the spectral widths of the 2D peaks over the graphene layer showed that strain fluctuations were more pronounced in the graphene with large domain size. It was observed that the mobility (sheet resistance) was decreased (increased) for the graphene with large domain size. The degradation of the electrical transport properties of the graphene with large domain size is mainly due to the defects, tensile strains, and local strain fluctuations within the individual domains.
Keywords: CHEMICAL-VAPOR-DEPOSITION; POLYCRYSTALLINE GRAPHENE; GROWN GRAPHENE; TRANSPORT-PROPERTIES; GRAIN-BOUNDARIES; SIZE; FILMS